Plutarch z Cheronei (Demetr. 32. 5–7) i wojna diadochów w latach 299–298 p.n.e. - Tomasz Zieliński (Studia Antiquitatis et Medii Aevi Incohantis, 2020)
Plutarch of Chaeronea (Demetr. 32.5–7) and the Diadochi War in 299-298 B.C.): The main issue of this article is response to the assumption of some researchers about the Diadochi War in 299-298 B.C. The analysis of our sources demonstrates that there are no sufficient evidences to such conclusions.